Elite Schooling and Social Inequality Privilege and Power in Ireland's Top Private Schools - Courtois, Aline (Palgrave Macmillan UK, 2018)
This book is the first significant sociological study of Ireland's elite private schools. It takes the reader behind the gates of these secretive institutions, and offers a compelling analysis of their role in the reproduction of social inequality in Ireland. From the selection process to past pupils' union events, from the dorms to the rugby pitch, the book unravels how these schools gradually reinforce exclusionary practices and socialize their students to power and privilege. It tackles the myths of meritocracy and classlessness in Ireland, while also providing keys to understanding the social practices and legitimacy of elites. By bringing out the voices of past pupils, parents and school staff and incorporating vivid ethnographic descriptions, the book provides a rare snapshot into a privileged world largely hidden from view. It offers a unique contribution to research on elite education as well as to the broader fields of sociology of education and inequality. As such, it will appeal to researchers, practitioners and the general public alike, in Ireland and beyond. .